PELATIHAN DAN PENDAMPINGAN INTREGASI MARKETING MIX UNTUK MENINGKATKAN DAYA SAING UMKM PADA ERA DIGITAL - Moh. Ainul Fais; I Gusti Ayu Sri Deviyanti; Nyoman Sri Widari; Agus Rahmanto; Wiwik Prihartanti (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2024)
This community service aims to provide understanding, training, and mentoring to MSMEs in RT 04 RW 14, Kalirungkut sub-district, as an effort to improve the understanding of MSME actors regarding the Marketing Mix in order to face the digitalization era. Through the KKN-PPM program of WR Supratman University Surabaya, the activities carried out after conducting observations include 5 stages of training that are carried out and approximately 26 days of mentoring process for which there are MSME consultations, training in the use of digital tools and software, formation of MSME business communities, and monitoring and evaluation of performance. The results found that MSMEs feel the benefits obtained starting from marketing methods, pricing, and openness to digital media that can improve sales performance from MSMEs, MSME actors around said they were able to see the direction and goals of the company in the future and know how to maintain the company's existence so that it remains optimal every year.